ESTIMASI HARGA JUAL LISTRIK DARI SAMPAH PENDUDUK KOTA PALANGKA RAYA - Fandi K. P. Asiaka (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
This study aims to predict the selling price of electricity from waste from residents of Palangka Raya City based on Presidential Regulation Number 35 Year 2018 concerning the Acceleration of the Development of Waste Processing Installations into Electric Energy Based on Environmentally Friendly Technology.The research method is done by predicting the number of residents, the amount of waste generated by the population, as well as the conversion of the amount of electricity generated from waste management using the Sanitary Landfill, Anaerobic Digestion and Incirenation methods and their selling points.The results of data analysis show that the population of Palangka Raya City in the next 20 years (2038) is predicted to reach 475.901 people up to 508.573 people and the estimated amount of waste reaches 69.482 tons to 371.258 tons. The amount of electricity generated from waste from the residents of Palangka Raya City is predicted to reach 179.507 kWh up to 352.695.548 kWh, while the estimated selling value reaches USD 2,396,418 up to USD 4.708.485.566.